Takhrij Hadis tentang Tatacara Berpuasa - Muhammad Tohir Ritonga (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to learn about the Hadith and its contents about the fasting ceremony, to make a scheme of the Sunnah Hadith about fasting, and to explain the examination of Sunnah hadith about Fasting ceremonies. This type of research uses descriptive qualitative research methods with a library survey approach, i.e. research supported by literature related to research issues. The results of this study show that first, the hadiths that describe fasting rituals in particular in the at-tis’ah pole were found quite a lot. He who eats because he forgets to fast, then it is a "sedekah" from God. Third, from the schema sanad above, it can be known that the hadith of the priest ad-Darimi is "marfu" from the beginning to the end. It indicates that the hadith is muttashil. Fourthly, from the examination of the Sunnah hadith can be known that the virgins of the Hadith in the Sunan ad-Darimi above are the Wahith and 'is, thus this Hadith is the Makbul (diterima). Fifth, this Hadith speaks of a man who forgets fasting and then he eats and drinks, it does not belong to the one who cancels fasting because there is no element of arbitrariness. The results of this research are expected to contribute to the development of the science of the Hadith in particular the hadith concerning the fasting ceremony so that there are results of the examination of the hasith in the takhrij.